2003
DOI: 10.1074/jbc.m210431200
|View full text |Cite
|
Sign up to set email alerts
|

Two-step Dimerization for Autoproteolysis to Activate Glycosylasparaginase

Abstract: Glycosylasparaginase (GA) is an amidase and belongs to a novel family of N-terminal nucleophile hydrolases that use a similar autoproteolytic processing mechanism to generate a mature/active enzyme from a single chain protein precursor. From bacteria to eukaryotes, GAs are conserved in primary sequences, tertiary structures, and activation of amidase activity by intramolecular autoproteolysis. An evolutionarily conserved HisAsp-Thr sequence is cleaved to generate a newly exposed N-terminal threonine, which pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…15 Another important aspect is that the structure of the T152C mature enzyme had been shown to be identical with that of the wild-type enzyme. 35,36 Thus, the T152C precursor appears to be an excellent candidate for a crystallographic snapshot of a GA pre-autoproteolysis structure.…”
Section: Resultsmentioning
confidence: 99%
“…15 Another important aspect is that the structure of the T152C mature enzyme had been shown to be identical with that of the wild-type enzyme. 35,36 Thus, the T152C precursor appears to be an excellent candidate for a crystallographic snapshot of a GA pre-autoproteolysis structure.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the mutant AGA precursors, this rearrangement is severely reduced, preventing the cleavage into subunits. It has been shown that dimerization of two precursor molecules is a prerequisite for the cleavage, and some AGU mutations in the dimer interface prevent dimerization and thus activation22930. However, this appears not to be the case with T122K and AGU-Fin, which both become processed into subunits when coexpressed with the wildtype AGA.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-linking of proteins was carried out according to the method of Wang and Guo (2003) with slight modification. Briefly, cross-linking was performed at approximately 0.1 mg/ml protein and 0.001% glutaraldehyde in 50 mM potassium-phosphate buffer (pH 7.5), and incubated for 4 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%